Implementation of the 2013 Curriculum in Integrated Thematic Learning in Elementary Schools: Strategies, Challenges, and its Impact on Learning - Lestari, Putu Eka; Yusuf, Yusni Arni; Ningsih, Yuliani Rahayu; Almuhsona, Lyra Guswita; Ningrum, Indah Larasati Kusuma (LPPPIPublishing, 2024)
Education is the process of imparting knowledge, character development, and producing a more harmonious social order and way of life, including through the development of students' intellectual capital, skills, and intellectual development. One of the innovations brought by the introduction of the 2013 curriculum is the integrative theme learning model. To provide meaningful educational experiences to students, integrative thematic learning connects various disciplines and materials through themes. The 2013 curriculum states that in order to place students as the center of the learning process, teachers must play an active role as facilitators and motivators of learning. This article aims to explain how the 2013 curriculum is applied to integrative thematic learning, and its impact on the teaching and learning process in elementary schools. The implementation of the curriculum in integrative thematic learning shows several challenges, such as difficulties in determining assessment or evaluation criteria for students, teachers' lack of understanding in compiling thematic integrative lesson plans, limited teaching aids, and the use of traditional learning methods that are less varied. The proposed solution is training and education for teachers, principals, and supervisors to acquire skills and knowledge in implementing the curriculum according to students' needs. By implementing a variety of learning methods, it is hoped that it can increase student motivation and independence in the learning process.